Wideband Crescent-Shaped Slotted Printed Antenna with Radiant Circular Polarisation - Asmeida, Akrem; Zainal Abidin, Zuhairiah; Mohd Shah, Shaharil; Kamarudin, Muhammad Ramlee; Abdul Malek, Norun; Nebhen, Jamel (Hindawi Limited, 2021)
Producing a suitable impedance matching between the radiating element and the feedline is the prior hurdle to overcome for a widebandantennawithcircularpolarisation designs. is study presents a novel antennaconsisting ofa defected groundstructure (DGS) and a crescent-slot radiating patch for broad impedance bandwidth. In addition, a narrow rectangular slot was etched on the ground plane for antenna compactness and outcomes improvement. In order to examine the reliability, two different numerical softwares were compared based on the antenna’s basic structure. Apart from this, an equivalent circuit of the proposed prototype is modelled logically using ADS 2016. e numerical results demonstrate that the impedance bandwidth was about 74.6% for<−10dB, while the 3dB axial ratio bandwidth greater than 53% was achieved. In the operational bandwidth of the design, good impedance matching and high efficiency were seen, which shows that this design is appropriate for modern wireless communication systems in ISM and GSM bands.